Structural and Spectroscopic Characterization of Co(II) Bis(Benzenedichlorodithiolate): An Intermediate in Hydrogen Evolution Catalysis - Virginia A. Larson; Jeff W. Kampf; Nicolai Lehnert (Inorganics, 2024)
Co bis(benzenedithiolate) type complexes have captivated chemists for decades for their interesting geometric and electronic structures and more recently, for their impressive ability to mediate the hydrogen evolution reaction (HER) both photo- and electrocatalytically. However, these complexes have nearly exclusively been characterized in their air-stable Co(III) oxidation states. In this work, Co(II) bis(benzenedichlorodithiolate) was prepared by chemical and electrochemical one-electron reduction. This reduced Co(II) complex was characterized by X-ray crystallography and in-depth spectroscopic studies—including UV-Vis, magnetic circular dichroism, and electron paramagnetic resonance spectroscopy. [Co(II)(Cl2bdt)2]2− is thereby shown to be a square planar complex, with a primarily metal-centered reduction, and an St = 1/2 spin state. This study informs our understanding of the first step in the HER catalytic cycle of Co bis(benzenedithiolate) type complexes and paves the way for future mechanistic studies on this catalyst family.